Sustainability of ecotourism in Endau-Rompin National Park: the awareness of nature and aboriginal culture conservation among tourists - Lai, Chee Sern; Mohd Salleh, Kahirol; Mohamad, Mimi Mohaffyza; Sulaiman, Nor Lisa; Abdul Razzaq, Abdul Rasid; Jailani, Md Yunos (Medwell Journals, 2018)
The awareness of nature and aboriginal culture conservation among tourist is important in order to sustain ecotourism in Endau-Rompin National Park. This research was conducted to measure the awareness levels of tourists in terms of nature conservation, aboriginal culture conservation and social development. A set of questionnaire was developed for data collection. A total of 50 tourist were voluntarily participated in this research. The findings revealed that high levels of awareness in nature conservation, aboriginal culture conservation and social development among tourists in Endau-Rompin National Park have been observed. This result reflects that the ecotourism in Endau-Rompin National Park is sustainable because the tourists are aware of the importance of protecting and conserving the nature, environment and culture that lead to social development for themselves.